Reakcja społeczności międzynarodowej na kryzys polityczny w Mjanmie po zamachu stanu z 2021 roku .......... 109 - Stefan, Krzysztof (Oblicza dyplomacji, 2025)
THE INTERNATIONAL COMMUNITY’S RESPONSE TO THE POLITICAL CRISIS IN MYANMAR FOLLOWING THE 2021 COUP D’ÉTATThe article discusses the international community’s response to the political crisis in Myanmar following the military coup on 1 February 2021. The author analyses the history of military rule in Myanmar leading up to the coup and its consequences, including the formation of a parallel National Unity Government (NUG) and the outbreak of civil war. Particular attention is given to the role of the United Nations (UN) and the Association of Southeast Asian Nations (ASEAN) in responding to the crisis. The author critically assesses the ineffectiveness of the UN, particularly the Security Council, and outlines the limited effectiveness of the Five-Point Consensus (5PC) proposed by ASEAN. The article also discusses the positions of key countries in the region, such as China, which, despite its economic cooperation with the democratic government of Aung San Suu Kyi, has supported the actions of the military junta for fear of losing influence in the region.